Advantages and Disadvantages of the Participation of SMEs in Tourism Clusters - HAVIERNIKOVÁ, Katarína; LEMAŃSKA-MAJDZIK, Anna; MURA, Ladislav (Journal of Environmental Management and Tourism; Vol 8 No 6 (2017): JEMT Volum VIII Issue 6(22) Fall 2017DO - 10.14505//jemt.v8.6(22).07, 2018)
The concept of clusters is based on creating entrepreneurship and competitiveness of interrelated organizations. The essence of the cluster initiative is to stimulate cooperation between individual enterprises and institutions, to accelerate innovation processes and thus to improve competitive position of enterprises operating within clusters. However, the participation in this initiative, based on the principle of cooperation, is also burdened with some negative effects resulting from the nature of cooperation and type of participants. The main aim of this paper is to evaluate the advantages and disadvantages of the participation in tourism clusters from the point of view of Slovak small and medium entrepreneurs. For evaluation, there were used the results of questionnaire surveys, which was interpreted by the Chi-Square test. The results showed that the most important advantages are from the areas of networking and common cooperation and propagation. The most important disadvantages were recognized mainly by micro and small entrepreneurs from the area of human resources.